РАЗРАБОТКА СИСТЕМЫ АВТОМАТИЧЕСКОГО РАСПОЗНАВАНИЯ РЕЧИ ДЛЯ КАРАКАЛПАКСКОГО ЯЗЫКА С ИСПОЛЬЗОВАНИЕМ Wav2Vec - Утеулиев, Н.У.; Кудайбергенов, Ж.К.; Кудайбергенов, Т.К. (SCIENCE and SOCIETY, 2025)
This paper presents a new approach to Automatic Speech Recognition (ASR) for the Karakalpak language, leveraging deep learning techniques, specifically the Wav2Vec model. The study outlines the methodology for capturing audio streams from a microphone, processing these audio files.
Keywords: ASR; Wav2Vec; recognition; model; frequency; metrics